Distribusi Beban Kerja dan Pengaruhnya terhadap Kinerja Aparatur Sipil Negara: Studi pada Dinas Sosial Kota Sukabumi - Purwanti, Dian; Tri, Rivany; Sirojul, Muhammad; Semedi, Adilla Bintang Putri (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2025)
The phenomenon of globalization and increasing societal demands have caused State Civil Apparatus (ASN) to face increasingly complex workloads, including within the Sukabumi City Social Service. Unequal workload distribution has the potential to reduce ASN motivation and well-being and disrupt the effectiveness of public services. This study used a quantitative approach through a survey of 20 ASN with a questionnaire instrument containing 12 questions. Data were analyzed using simple linear regression via SPSS version 30 to determine the effect of workload on ASN performance. The results showed that workload had a positive and significant effect on performance (β = 0.572; p < 0.001). The majority of ASN assessed that workload was still within reasonable limits, although there were indications of imbalance in the distribution of tasks among employees. These findings confirm that fair and proportional workload management is an important factor in increasing productivity while maintaining ASN welfare.